Autoimmune Hepatitis Markers in Association with Chronic Viral Hepatitis Type B and C - Omar M. Ali, Khalid (Tikrit Journal of Pharmaceutical Sciences, 2023)
Circulating auto-antibodies have gained great significance for the diagnosis of autoimmune hepatitis (AIH) and various autoantibodies have been reported in patients infected by chronic viral hepatitis. Enzyme linked immunosorbent assay (ELISA) was used to assess these autoantibodies in the sera of 116 seropositive hepatitis B & C virus patients admitted to Baghdad Teaching Hospital from March 2009 to the end of December 2009. The presence of autoantibodies against cell nuclei (ANA), smooth muscle (SMA), liver- cytosol type-1 (anti LC1) and liver kidney microsome type1 (anti LKM-1) for all the affected patients' sera was measured. Antinuclear antibodies (ANA) results showed that 18 (16%) of cases revealed seropositive results, while anti- smooth muscle antibodies (SMA) results showed only two (2%) seropositive results both of which are of HCV patients. Results of anti LC-1 autoantibodies and anti LKM1 autoantibodies showed seropositivity in 6 (5%) and 8 (7%) cases, respectively, all of which are of HCV type. The current study suggest that chronic HCV infection can mimic autoimmune chronic active hepatitis; and special care must be held in patients who are unresponsive to immunosuppressive treatment, as HCV may be the role here.